Educational opportunities for postgraduate medical trainees during the COVID-19 pandemic: deriving value from old, new and emerging ways of learning. Issue 1159 (3rd August 2021) - Kumar, Kartik; Groom, Katherine; Martin, Laura; Russell, Georgina K; Elkin, Sarah L
Abstract : The COVID-19 pandemic has had a significant impact on postgraduate medical training across all specialties. Although some traditional learning opportunities have been curtailed, there have been numerous examples of highly valuable educational experiences that have arisen during this time. Here, from a trainee perspective, we consider the educational merits of the re-emergence of 'firm-based' teams, new online learning opportunities, use of digital technologies and the rise of telephone clinics and new COVID-19 clinical services. As health services continue to recover from surges in COVID-19 cases, it is important to reflect on and recognise the value of these educational experiences so that helpful elements can be retained and embedded into training programmes for the benefit of both trainees and patients.